A bandwidth-tunable bioamplifier with voltage-controlled symmetric pseudo-resistors. Issue 6 (June 2015) - Shiue, Muh-Tian; Yao, Kai-Wen; Gong, Cihun-Siyong Alex
Abstract This paper describes a bioamplifier that employs a voltage-controlled-pseudo-resistor to achieve tunable bandwidth and wide operating voltage range for biomedical applications. The versatile pseudo-resistor employed provides ultra-high resistance for ac coupling to cancel the dc offset from electrode–tissue interface. The voltage-controlled-pseudo-resistor consists of serial-connected PMOS transistors working at the subthreshold region and an auto-tuning circuit that makes sure the constant (time-invariant) control-voltage of the pseudo-resistor. This bandwidth-tunable bioamplifier is designed in a 0.18-μm standard CMOS process, achieving a gain of 40.2 dB with 10.35-μW power consumption. The designed chip was also used to develop the proof-of-concept prototype. An operation bandwidth of 9.5 kHz, input-referred noise of 5.2 <alternatives><inline-graphic xlink:href="ark:/27927/pgj24fgpr8x" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μVrms</alternatives> from 6.3 Hz to 9.5 kHz and 5.54 <alternatives><inline-graphic xlink:href="ark:/27927/pgj24fgr1pn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μVrms</alternatives> from 250 Hz to 9.5 kHz, and a tunable cutoff-frequency from 6.3–600 Hz were demonstrated to prove our design.